Factors Affecting MinaIndividuals Using Sharia Financial Technology (Fintech) in Medan City Community - Rinsa Oos; Sriwardany (PT Inovasi Pratama Internasional, 2022)
This study aims to identify the factors that influence the interest of the people of the city of Medan in using Sharia Fintech . This study uses a quantitative descriptive approach. The population in this study were all the people of the city of Medan who met certain criteria as many as 70 people. Instruments and data collection is done by giving a questionnaire directly to the respondents. This study uses multiple linear regression analysis techniques, t test, F test, and the coefficient of determination. Based on the results of the multiple linear regression equation Y = -6.547 + 0.258 X 1 + 0.255 X 2 + 0.301 X 3 + 0.150 X 4 + 0.916 X 5 where the variables of social factors, trust, sharia compliance, security guarantees and habits have an influence on individual interest variables . Based on the results of the partial test (t test) shows that social factors have a positive and significant effect on individual interest. It can be seen from r count > r table ( 4.201 > 1.997) with a significant level of 0.000 < 0.05. Based on the results of the coefficient of determination test, it is known that the R square value is 0.646. This means that the influence of social factors, trust, sharia compliance, security guarantees and habits on individual interests is 64.6%, while the remaining 35.4% is influenced by other variables not included in this study.